Effects of a 5-minute classroom-based physical activity on on-task behaviour and physical activity levels - Podnar, Hrvoje, kineziolog; Novak, Dario, kineziolog; Radman, Ivan, kineziolog (2018)
The objective was to explore the effectiveness of a five-minute classroom-based physical activity (5min-Class-PA) to keep student behaviour on task while increasing PA and energy expenditure during school days. The multiple baselines across subjects’ design was implemented to assess on-task behaviour during academic lessons (e.g., Mathematics, Science, Language, Art). Observers were blinded to study condition. A quasi-experimental design was implemented to assess PA volume and energy expenditure using SenseWear Armband body monitor (BodyMedia Inc., Pittsburgh, PA, USA). A convenience sample of elementary school pupils (aged 6-10 years) was observed. A total of eight class departments or two class departments per grade (first to fourth) were included by random selection. All pupils from the selected class departments were asked to participate (total 149) and 126 (85%) had no health aberrations and returned parent signed informed agreement on participation. Five-minute PA daily was performed in the middle of a 45-min academic lesson by imitating video animations projected on the school board for 12 weeks. The aims were to assess on-task behaviour during academic lessons and physical activity volume and energy expenditure during a school day. When the 5min-Class-PA was implemented, initially high on-task behaviour during the first part of the lesson (91.42% and 94.8% for 6-8- and 8-10-year-olds, respectively) was not significantly changed after the 5min-Class-PA. In contrast, when the 5min-Class-PA was not implemented, on-task behaviour during the second part of the lesson decreased (by 3% and 4% for 6-8- and 8-10-year-olds, respectively). After the 5min-Class-PA was systematically introduced, on-task behaviour systematically improved. The results of the implementation of the classroom-based PA also indicated a small, non-significant increase in PA levels and energy expenditure during the school day, but also a non-significant increase in sedentary time.
Bibliografija: str. 258-259
Keywords: Tjelesna aktivnost -- Učenici -- Školski uspjeh